MASIHKAH HIPOTESIS AKUNTANSI POSITIF BISA MENJELASKAN MANAJEMEN LABA? - Fajar Dwi Nurmanto (Media Riset Akuntansi, Auditing & Informasi, 2018)
This study examines the effect of executive compensation, firm size, corporate value and leverage to earning management with good corporate management as a moderating at manufacturing companies listing on Indonesia Stock Exchange (IDX).This study used a sample of manufacturing companies listed on the Indonesia Stock Exchange during the period 2014-2016. Sample was determined by using purposive sampling method. The study has 159 samples from 53 companies. In this study, hypotheses were tested using multiple regression.This study used a method developed by Stubben (2010) for the measurement of earnings management, with earnings management approach using revenue discretionary model and conditional revenue model, where the results show that executive compensation, firm size and leverage significantly effect earnings management, while the corporate value has no effect on earnings management. Good corporate governance is also proven to affect leverage and earnings management relationships, but it can not affect executive compensation, firm size and corporate value of earnings management.